PENGARUH EARNINGS MANAGEMENT TERHADAP KINERJA - Aida Ainul Mardiyah (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2005)
This research is aimed at giving empirical evidence that earning management does influence performance. The 153 sample from 1997 to 2001 is determined by using stratified random sampling. Multiple regression analysis is used to test hypotheses based on this archival data. The result of the analysis shows that earning management influences performance. This is in line with Barnea et al. (1976), Mones (1987), Ilmainir (1993), Hapworth (1953) in Ashari et al. (1994), Arhibald (1967) in Ashari et al. (1994), Ashari et al. (1994: 292), Zuhroh (1996), Jin (1997), Godfrey and Jones (1999), Defond and Jiambalvo (1994) in Scott (2000), Sweeney (1994) in Scott (2000), Ghofar (2001), Tarjo (2002), and Mardiyah (2003) which also conlude that earning managementinfluences performance.Keywords: earnings management, performance, stratified random sampling.